O Role Play em anatomia humana: promovendo aprendizagem colaborativa e engajamento estudantil - Morano, Arnilza Torres Amaral (2024)
Role Play (RP) is an educational methodology that allows students to experience realistic situations, immerse themselves in engaging narratives, contextualizing, and giving meaning to everyday experiences. This approach integrates practical experience and emotional immersion, making students' learning and protagonist more impactful and memorable. The overall aim of this study is to investigate the impact of Role Play on student learning and motivation in the subject of Human Anatomy (HA). In this context, we propose a quasi- experimental exploratory study with a qualitative and quantitative approach to investigate the effects of role play on learning concepts about the endocrine system in the subject of human anatomy. The methodology was developed with the participation of 98 students from the Dentistry and Pharmacy courses, where 45 dentistry students took the conventional class and 53 pharmacy students took the conventional class and the intervention with PR, from the Federal University of Ceará (UFC), divided into four groups of free choice. Each group was responsible for planning an anatomical situation to be explored through RP, enriched with narrative elements. The activity was structured in three stages: literature review, conventional class and Role Play. Data analysis used inferential statistics, considering results with a p-value < 0.05 to be significant when compared to the use of RP. For the content analysis of satisfaction, the percentage response model was used, finding an average value of 98% approval of the methodology applied. The conclusion of the study was based on the application of RP as an educational tool for teaching content relating to the endocrine system and explored the synergy between practical experiences and engaging narratives as an innovative strategy to improve understanding and the active engagement of students. Therefore, the study, being innovative, still needs to be explored in other areas of interest in Anatomy, but for the research model developed here it was prescriptive.